Biofilm formed on different natural substrates enhances the growth and survival in Macrobrachium rosenbergii (de Man, 1879) juveniles - Jesna, P. K.; Pillai, B. R.; Naik, Namita; Pradhan, Harmohan (Indian Journal of Fisheries, 2018)
An experiment of 65 days duration was conducted to study the effect of biofilm formed on different natural substrates at different substratum densities on the growth and survival of juveniles of freshwater prawn Macrobrachium rosenbergii (de Man, 1879). Natural substrates like dried paddy straw and cut grass were evaluated as substratum for biofilm production. The experiment was conducted in fiber glass tanks of 500 l capacity. The study comprised six treatments viz., dried paddy straw at 60 (T1); 120 (T2) and 240 (T3) g tank-1 and cut grass at 60 (T4) and 120 (T5) g tank-1, each with three replicates following a completely randomised design. Prawn juveniles reared without any substratum acted as control. Ten days after the introduction of substratum in the tanks, prawn juveniles (2.01 g±0.37) were stocked at a density of 40 m-³. The juveniles were fed with 2 mm commercial pellet feed (30% protein) at 5% of the biomass. No water exchange was done in the treatment tanks whereas in control tanks 50% water exchange was done once every week. The study revealed significantly (p<0.05) higher survival rate (%) in the treatment tanks (94.4±9.6, 80.5±12.7, 86.1±12.7, 86.1±4.8 and 91.6±8.35 for treatments T1, T2, T3, T4 and T5 respectively) compared to the control (52.8±9.5). Among treatment tanks, T2 and T3 showed significantly higher (p<0.05) average daily growth (g d-1) (0.055±0.005 and 0.057±0.005 respectively) when compared to other treatments (0.0367±0.02 for T1 and 0.0373±0.01 for T5). But the specific growth rate did not show any significant difference among the treated groups including control. Use of biofilm significantly reduced the usage of water (by 2.9 times) compared to control, which is significant considering the predicted water scarcity in future.